التحول الطاقوي كآلية لتحقيق التنمية المستدامة: دراسة تحليلية - مالكي, عمر; مؤذن, عمر (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى معرفة عوامل تحقيق التحول نحو استخدام الطاقة المتجددة بدلا من الوقود الأحفوري، وكيف يمكن لهذا التحول أن يسهم في تحقيق التنمية المستدامة، وهذا من خلال تحليل تطور بعض المؤشرات في العالم وفي الجزائر. توصلنا من خلال هذا التحليل إلى أن الطاقة المتجددة تعتبر بديلا مناسبا للطاقة الأحفورية كونها تمتلك صفة التجدد والديمومة، كما أشارت التحاليل أن الجزائر لا تزال بعيدة في هذا المجال مقارنة بدول أخرى، ما يحتم عليها بذل المزيد من الجهد في سبيل تحقيق عوامل نجاح هذا التحول. تصنيف JEL: E26، C97. Abstract: This study aims to know the factors of achieving the shift towards the use of renewable energy instead of fossil fuels, and how this shift can contribute to achieving sustainable development, and this by analyzing the evolution of some indicators in the world and in Algeria; we found through this analysis that renewable energy It is considered a suitable alternative to fossil energy because it has the character of renewal and permanence, as analyzes indicated that Algeria is still far in this area compared to other countries, which requires more effort to achieve the factors of success of this transformation. Keywords: Energy Transformation, Renewable Energy, Fossil Fuels, Sustainable Development, energy consumption. Jel Classification Codes: E26، C97.
Keywords: ةالتحول الطاقوي، الطاقة المتجددة، الوقود الأحفوري، التنمية المستدامة، استهلاك الطاقة.